Faithful Resilience: Profit and Support Strategies of Religious Institutions amidst the COVID-19 Crisis - Beuy Joob; Viroj Wiwanitkit (UIN Sunan Gunung Djati Bandung, 2023)
This article presents an analysis of the observation on making a profit for religious institutions and providing social support during the COVID-19 pandemic in a tropical country in Indochina. The study utilizes a descriptive approach, combining a literature review and a case study to explore the specific situation in the region. The article begins with an introduction to the concept of social marketing and then focuses on a unique form of religiously related social marketing: the production and sale of amulets. The potential benefits for religious establishments in terms of both financial gain and social support are highlighted. Furthermore, a detailed case study on ritual amulet marketing during the COVID-19 outbreak crisis is provided, shedding light on the strategies employed and the outcomes achieved. The findings suggest that social marketing by religious institutions can be a valuable advertising tool even during times of public crisis. The article concludes by emphasizing the potential of social marketing as an effective means for religious institutions to address societal needs and generate positive impacts. This research contributes to the understanding of the role of religious organizations in the promotion of social welfare and offers insights for practitioners seeking innovative approaches to navigate challenging circumstances.